Pengaruh Pengetahuan Kewirausahaan, Efikasi Diri, dan Literasi Digital terhadap Intensi Berwirausaha Mahasiswa Prodi Pendidikan Ekonomi Universitas Negeri Surabaya: Penelitian - Khoirotun Nisa'; Norida Canda Sakti (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the influence of entrepreneurial knowledge, self-efficacy, and digital literacy on entrepreneurial intentions among students in the Economics Education Study Program at Surabaya State University. This study used a quantitative approach with multiple linear regression analysis using SPSS software. The population in this study were students from the class of 2021 who had taken entrepreneurship courses, with a sample size of 81 students. The results showed that partially, entrepreneurial knowledge did not significantly influence entrepreneurial intentions. However, self-efficacy and digital literacy significantly influenced entrepreneurial intentions. Simultaneously, entrepreneurial knowledge, self-efficacy, and digital literacy significantly influenced entrepreneurial intentions. These findings also indicate that self-efficacy and digital literacy play an important role in shaping students' entrepreneurial intentions.